Ethylene-vinyl ester copolymer saponified pellets and films thereof
By controlling the turbidity of ethylene-vinyl ester-based copolymer saponified pellets in the aqueous methanol solution and adding a moderate amount of polymerization inhibitors during the polymerization process, excessive gel production is solved when the pellets of ethylene-vinyl ester-based copolymer pellets form films, the The problem is that the film quality with low gel quantity and low oxygen transmittance is achieved.
Patent Information
- Application Number
- CN202110513512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-05-11
AI Technical Summary
When the existing ethylene-vinyl ester-based copolymer pellets form films, the gel is often produced too much due to excessive aggregates, which affects the film quality and oxygen transmittance.
By controlling the turbidity of ethylene-vinyl ester-based copolymer saponified pellets in the aqueous methanol solution, we ensure that the turbidity is less than 300 NTU when the ethylene content is 24 to 35 mole%, or the turbidity is less than 200 NTU when the ethylene content is 36 to 48 mole%. , and the polymerization inhibitor is added in an appropriate amount during the polymerization process to mix evenly to reduce the formation of aggregates.
It effectively reduces the amount of gel and oxygen transmittance in the film, improves the quality of the film, and ensures the gas barrier and uniformity of the film.
Smart Images

Figure BDA0003061217690000111 
Figure BDA0003061217690000122
Abstract
Description
Technical Field
[0001] The present invention relates to a saponified ethylene-vinyl ester copolymer, in particular to pellets of the saponified ethylene-vinyl ester copolymer having a specific turbidity when dissolved in a methanol aqueous solution. The present invention also discloses a film formed from the pellets of the saponified ethylene-vinyl ester copolymer. Background Art
[0002] Ethylene-vinyl ester copolymers, such as ethylene vinyl alcohol copolymer (EVOH) resins, are widely used in multilayer bodies for preserving perishable items. For example, EVOH resins and multilayer bodies are commonly used in the food packaging industry, medical equipment and consumables industry, pharmaceutical industry, electronics industry, and agricultural chemical industry. EVOH resins are often used to be added to multilayer bodies as a distinct layer to act as an oxygen barrier layer.
[0003] It is known that EVOH pellets / granules formed from EVOH resin often contain a large amount of aggregates, which results in a large amount of gel in the subsequent film formed from the EVOH pellets, resulting in poor quality. Summary of the invention
[0004] The inventors have discovered that known EVOH films have poor quality due to uneven mixing or insufficient addition of polymerization inhibitors during the EVOH manufacturing process, a large amount of aggregates contained in EVOH pellets, a high amount of gel in the EVOH film and / or a high oxygen permeability (also referred to herein as oxygen transmission rate) of the EVOH film.
[0005] There is a continuing need for a film that can provide pellets of ethylene-vinyl ester copolymer saponified product with a small amount of gel and a low oxygen transmission rate (OTR).
[0006] The present invention relates to an ethylene-vinyl ester copolymer saponified pellet, wherein the ethylene content of the pellet is 24-35 mole%, and the turbidity of the pellet in a 60% (w / w) methanol aqueous solution is less than 300 NTU; or the ethylene content of the pellet is 36-48 mole%, and the turbidity of the pellet in a 80% (w / w) methanol aqueous solution is less than 200 NTU. In some cases, the ethylene-vinyl ester copolymer saponified pellet has an ethylene content of 24-35 mole%, and the turbidity of the pellet in a 60% (w / w) methanol aqueous solution is 0.5-120 NTU; or the ethylene content of the pellet is 36-48 mole%, and the turbidity of the pellet in a 80% (w / w) methanol aqueous solution is 0.5-120 NTU. The ethylene-vinyl ester copolymer saponified pellet can be used to prepare a film or a multilayer structure.
[0007] In addition or alternatively, the pellets include a polymerization inhibitor in an amount of 1 to 850 ppm. In a preferred embodiment, the pellets include a polymerization inhibitor in an amount of 5 to 650 ppm. The polymerization inhibitor is a conjugated polyene. The polymerization inhibitor may be sorbic acid, cinnamic acid, 1,3-hexadiene or myrcene. According to at least one embodiment, the polymerization inhibitor is added and mixed by a mixer, which is a dynamic mixer or a static mixer. In some embodiments, the length to radius ratio of the mixer is 1.3 to 65 L / D.
[0008] According to at least one embodiment, the ethylene-vinyl ester copolymer saponified pellets have an ethylene content and a saponification degree, wherein the ethylene content is about 24 to about 48 mole %, and the saponification degree is 99.5 mole % or higher.
[0009] In addition, according to at least one embodiment, the ethylene-vinyl ester copolymer saponified pellets may further have a boron content of 10-450 ppm. In some cases, in addition to the boron content of 10-450 ppm, the ethylene-vinyl ester copolymer saponified pellets may further contain alkali metals, lubricants, alkaline earth metals, salts thereof and / or mixtures thereof.
[0010] In another aspect of the present invention, a film formed from the ethylene-vinyl ester copolymer saponified pellets as described above is provided. In some preferred embodiments, the oxygen transmission rate (OTR) of the film is less than 3.4 cm at 23°C and 65% relative humidity according to ISO 14663-2. 3 *20μm / m 2 *24Hr*atm.
[0011] In addition or alternatively, the present invention provides a film formed from the above-mentioned ethylene-vinyl ester copolymer saponified pellets, wherein the number of gels in the film is less than 1180 / m 2 In some cases, the number of gels in the membrane is less than 600 / m 2 .
[0012] According to at least one embodiment, the multilayer structure includes: (a) at least one layer formed by the ethylene-vinyl ester copolymer saponified pellets as described above; (b) at least one polymer layer; and (c) at least one adhesive layer. The polymer layer can be, for example, selected from the group consisting of a low-density polyethylene layer, a polyethylene grafted maleicanhydride layer, a polypropylene layer, and a nylon layer. The adhesive layer is a tie layer.
[0013] It was unexpectedly found that in the manufacturing process of ethylene-vinyl ester copolymer saponification, a large amount of initiator is added during polymerization to react, and the polymerization output contains a large amount of initiator, and an inhibitor is added to terminate the reaction. At this time, if the inhibitor is added sufficiently and the polymerization output is mixed evenly with the inhibitor, the reaction can be terminated and no aggregates will be generated, and the ethylene-vinyl ester copolymer saponification will not produce gel after film formation; if the inhibitor is not added enough or the polymerization output is mixed unevenly with the inhibitor, the reaction cannot be terminated, and the reaction will continue to react and produce aggregates, and the ethylene-vinyl ester copolymer saponification will produce gel after film formation. In view of this, the inventor believes that no matter how the polymerization conditions and inhibitor addition conditions change, as long as the turbidity of the ethylene-vinyl ester copolymer saponification pellets dissolved in methanol water is ensured to be within a certain range, it means that the content of aggregates in the ethylene-vinyl ester copolymer saponification is low, and the purpose of reducing the number of gels produced after film formation and lower oxygen permeability is achieved. DETAILED DESCRIPTION
[0014] The present invention provides an ethylene-vinyl ester copolymer saponified product, specifically, for example, an ethylene-vinyl alcohol copolymer (EVOH), the ethylene-vinyl ester copolymer saponified product can be in the form of particles / pellets, films, fibers, etc. The ethylene-vinyl ester copolymer saponified product described herein is granulated to form one or more pellets and / or shapes. Although the ethylene-vinyl ester copolymer saponified product is described throughout the present invention as being granulated to form one or more ethylene-vinyl ester copolymer saponified product pellets, the ethylene-vinyl ester copolymer saponified product can be processed into beads, cubes, chips, shavings, etc.
[0015] In some cases, the ethylene-vinyl ester copolymer saponified product is in the form of pellets, which have a specific turbidity, particularly an ethylene content of 24-35 mole%, and the turbidity of the pellets dissolved in a 60% (w / w) methanol aqueous solution is less than 300 NTU; or an ethylene content of 36-48 mole%, and the turbidity of the pellets dissolved in an 80% (w / w) methanol aqueous solution is less than 200 NTU. The ethylene-vinyl ester copolymer saponified product pellets can be used to prepare films.
[0016] The pellets have an ethylene content of 24 to 35 mole%, and the turbidity of the pellets dissolved in 60% (w / w) methanol aqueous solution is, for example, less than 300 NTU, less than 275 NTU, less than 250 NTU, less than 225 NTU, less than 200 NTU, less than 175 NTU, less than 150 NTU, less than 125 NTU, less than 100 NTU, less than 75 NTU, less than 50 NTU, less than 25 NTU, less than 20 NTU, less than 15 NTU, less than 10 NTU or less than 1 NTU. The pellets have an ethylene content of 36 to 48 mole %, and the turbidity of the pellets dissolved in 80% (w / w) methanol aqueous solution is lower than 200 NTU, for example, lower than 200 NTU, lower than 175 NTU, lower than 150 NTU, lower than 125 NTU, lower than 100 NTU, lower than 75 NTU, lower than 50 NTU, lower than 25 NTU, lower than 20 NTU, lower than 15 NTU, lower than 10 NTU or lower than 1 NTU.In a preferred embodiment, the ethylene-vinyl ester copolymer saponified pellets have an ethylene content of 24-35 mole%, and the turbidity of the pellets dissolved in 60% (w / w) methanol aqueous solution is 0.5-120 NTU, for example: 0.5-120 NTU, 0.5-100 NTU, 0.5-80 NTU, 0.5-60 NTU, 0.5-40 NTU, 0.5-20 NTU, 1-120 NTU, 1-100 NTU, 1-80 NTU, 1-60 NTU, 1-4 0NTU, 1~20NTU, 5~120NTU, 5~100NTU, 5~80NTU, 5~60NTU, 5~40NTU, 5~20NTU, 10~120NTU, 10~100NTU, 10~80NT U, 10~60NTU, 10~40NTU, 10~20NTU, 25~120NTU, 25~100NTU, 25~80NTU, 25~60NTU, 25~40NTU, 50~120NTU, 50~10 0NTU or 50-80NTU; or its ethylene content is 36-48 mole%, and the turbidity of the pellets dissolved in 80% (w / w) methanol aqueous solution is 0.5-120NTU, for example: 0.5-120NTU, 0.5-100NTU, 0.5-80NTU, 0.5-60NTU, 0.5-40NTU, 0.5-20NTU, 1-120NTU, 1-100NTU, 1-80NTU, 1-60NTU, 1-40NTU, 1-20NTU, 5 ~120NTU, 5~100NTU, 5~80NTU, 5~60NTU, 5~40NTU, 5~20NTU, 10~120NTU, 10~100NTU, 10~80NTU, 10~60NTU, 10~40NTU, 10~20NTU, 25~120NTU, 25~100NTU, 25~80NTU, 25~60NTU, 25~40NTU, 50~120NTU, 50~100NTU or 50~80NTU.
[0017] The formation of aggregates in EVOH pellets may be affected by complex factors such as EVOH with low ethylene content, EVOH with high polymerization degree, EVOH with high ethylene content, or dehydrated cross-linked EVOH. Although not limited by any particular theory, the inventors believe that as long as the turbidity value of the ethylene-vinyl ester copolymer saponified pellets dissolved in methanol water is within the desired range, the content of aggregates in the ethylene-vinyl ester copolymer saponified pellets can be ensured to be low, thereby achieving the purpose of reducing the amount of gel produced after film formation and lowering the oxygen permeability.
[0018] The ethylene-vinyl ester copolymer saponified pellets have an ethylene content. For example, the ethylene content of the EVOH may be about 24 to about 48 mole%, about 20 to about 50 mole%, about 25 to about 45 mole%, about 28 to about 42 mole%, or about 30 to about 40 mole%. The ethylene content is, for example, 24 mole%, 25 mole%, 26 mole%, 27 mole%, 28 mole%, 29 mole%, 30 mole%, 31 mole%, 32 mole%, 33 mole%, 34 mole%, 35 mole% or between any two of the foregoing values; or for example, 35 mole%, 36 mole%, 37 mole%, 38 mole%, 39 mole%, 40 mole%, 41 mole%, 42 mole%, 43 mole%, 44 mole%, 45 mole%, 46 mole%, 47 mole%, 48 mole% or between any two of the foregoing values.
[0019] Additionally or alternatively, the saponification degree of the EVOH resin composition 100 may be 90 mole % or higher, preferably 95 mole % or higher, preferably 97 mole % or higher, and preferably 99.5 mole % or higher.
[0020] The ethylene-vinyl ester copolymer saponified pellets include a polymerization inhibitor in an amount of 1 to 850 ppm, for example, 1 to 850 ppm, 1 to 800 ppm, 1 to 750 ppm, 1 to 700 ppm, 1 to 650 ppm, 1 to 600 ppm, 1 to 550 ppm, 1 to 500 ppm, 1 to 450 ppm, 1 to 400 ppm, 1 to 350 ppm, 1 to 300 ppm, 1 to 250 ppm, 1 to 200 ppm, 1 to 150 ppm, 1 to 100 ppm, 1 to 50 ppm, 5 to 850 ppm, 5 to 800 ppm, 5 to 750 ppm, 5 to 700ppm, 5~650ppm, 5~600ppm, 5~550ppm, 5~500ppm, 5~450ppm, 5~400ppm, 5~350ppm, 5~300ppm, 5~250ppm, 5~200ppm, 5~150ppm, 5~100p 5 0~350ppm, 50~300ppm, 50~250ppm, 50~200ppm, 50~150ppm, 50~100ppm, 10~850ppm, 10~800ppm, 10~750ppm, 10~700ppm, 10~650ppm, 10~ 600ppm, 10~550ppm, 10~500ppm, 10~450ppm, 10~400ppm, 10~350ppm, 10~300ppm, 10~250ppm, 10~200ppm, 10~150ppm, 10~100ppm, 10~50 In a preferred embodiment, the ethylene-vinyl ester copolymer saponified product pellets include a polymerization inhibitor in an amount of 5 to 650 ppm.The polymerization inhibitor is a conjugated polyene, for example, 2,3-dimethyl-1,3-butadiene, 2-tert-butyl-1,3-butadiene, 1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-pentadiene, 3-ethyl-1,3-pentadiene, 2-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 1,3-hexadiene, 2,5-dimethyl-2,4-hexadiene, 1,3-octadiene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,4-diphenyl-1,3-butadiene, 1-methoxy-1,3-butadiene, 2-methoxy-1,3-butadiene, diene, 1-ethoxy-1,3-butadiene, 2-ethoxy-1,3-butadiene, 2-nitro-1,3-butadiene, chloroprene, 1-chloro-1,3-butadiene, 1-bromo-1,3-butadiene, isoprene, tropone, ocimene, fulvene, ferrandrene, myrcene, farnesene, phllandrene, cembrene, sorbic acid, sorbic acid esters, sorbic acid salts, abietic acid The conjugated polyenes include sorbic acid, sorbic acid esters, sorbic acid salts and other sorbic acid compounds, cinnamic acid, 1,3-hexadiene or myrcene.
[0021] The polymerization inhibitor is added by mixing through a mixer, which is a dynamic mixer, a general static mixer or a Noritake static mixer. To achieve a better mixing effect, the mixer has a specific length to diameter ratio, for example: 1-70L / D, 1-65L / D, 1-60L / D, 1-50L / D, 1-40L / D, 1-30L / D, 1-20L / D, 1-10L / D, 1.3-70L / D, 1.3-65L / D, 1.3-60L / D, 1.3-50L / D, 1.3-40L / D, 1.3-30L / D, 1.3-20L / D, 1.3~10L / D, 5~70L / D, 5~65L / D, 5~60L / D, 5~50L / D, 5~40L / D, 5~30L / D, 5~20L / D, 5~10L / D, 20~70L / D , 20~65L / D, 20~60L / D, 20~50L / D, 20~40L / D, 40~70L / D, 40~65L / D, 40~60L / D, 40~50L / D or 60~70L / D.
[0022] The ethylene-vinyl ester copolymer saponified pellets may contain boron compounds and / or boric acid and / or cinnamic acid and / or alkali metals and / or conjugated polyenes and / or lubricants and / or alkaline earth metals in some cases. The above substances can give the ethylene-vinyl ester copolymer saponified pellets better properties. The above substances are common substances that are usually present in ethylene-vinyl ester copolymer saponified pellets, giving them better properties. If the content of the above conjugated polyene structure compound is 1 to 30,000 ppm per unit weight of the ethylene-vinyl ester copolymer saponified pellets, the coloring after heating can be further suppressed, and the thermal stability is more excellent. If the content of the above alkali metal compound or alkaline earth metal compound is 1 to 1000 ppm per unit weight of the ethylene-vinyl ester copolymer saponified pellets in terms of metal conversion, it can become a more excellent long-term operation formability. The lubricant can achieve further excellent processability when the content of the lubricant in the pellets of the saponified ethylene-vinyl ester copolymer is 1 to 300 ppm per unit weight.
[0023] In addition or alternatively, according to other aspects of the present invention, the ethylene-vinyl ester copolymer saponify pellets may have a boron content of 10 to 450 ppm. Without being limited to any particular theory, it is believed that adding a boron compound to the ethylene-vinyl ester copolymer saponify pellets to make the boron content 10 to 450 ppm reduces or eliminates the sticking phenomenon during the extrusion process through the screw extruder, and further improves the uniformity and flexibility of the film thickness. In some cases, the boron content of the ethylene-vinyl ester copolymer saponify pellets may be 10 to 450 ppm, 10 to about 400 ppm, 10 to about 350 ppm, 10 to about 300 ppm, 10 to about 275 ppm, 10 to about 250 ppm, 10 to about 225 ppm, 10 to about 200 ppm, 10 to about 175 ppm, about 20 to 450 ppm, about 20 to about 400 ppm, about 20 to about 350 ppm, based on the total weight of the ethylene-vinyl ester copolymer saponify pellets. about 20 to about 300 ppm, about 20 to about 275 ppm, about 20 to about 250 ppm, about 20 to about 225 ppm, about 20 to about 200 ppm, about 20 to about 175 ppm, about 60 to 450 ppm, about 60 to about 400 ppm, about 60 to about 350 ppm, about 60 to about 300 ppm, about 60 to about 275 ppm, about 60 to about 250 ppm, about 60 to about 225 ppm, about 60 to about 200 ppm, about 60 to about 175 ppm, about 100 to about 100 to about 450 ppm, about 100 to about 400 ppm, about 100 to about 350 ppm, about 100 to about 300 ppm, about 100 to about 275 ppm, about 100 to about 250 ppm, about 100 to about 225 ppm, about 100 to about 200 ppm, about 100 to about 175 ppm, about 140 to 450 ppm, about 140 to about 400 ppm, about 140 to about 350 ppm, about 140 to about 300 ppm, about 140 to about 275 ppm, about 14 ... ppm, about 140 to about 225 ppm, about 140 to about 200 ppm, about 180 to about 450 ppm, about 180 to about 400 ppm, about 180 to about 350 ppm, about 180 to about 300 ppm, about 180 to about 275 ppm, about 180 to about 250 ppm, about 180 to about 225 ppm, about 220 to 450 ppm, about 220 to about 400 ppm, about 220 to about 350 ppm, about 220 to about 300 ppm, about 220 to about 275 ppm.
[0024] In some cases, the boron compound may include boric acid or a metal salt thereof. Examples of metal salts include, but are not limited to, calcium borate, cobalt borate, zinc borate (e.g., zinc tetraborate, zinc metaborate), potassium aluminum borate, ammonium borate (e.g., ammonium metaborate, ammonium tetraborate, ammonium pentaborate, ammonium octaborate), cadmium borate (e.g., cadmium orthoborate, cadmium tetraborate), potassium borate (e.g., potassium metaborate, potassium tetraborate, potassium pentaborate, potassium hexaborate, potassium octaborate), silver borate (e.g., silver metaborate, silver tetraborate), copper borate (e.g., copper (II) borate, copper metaborate, copper tetraborate), sodium borate (e.g., sodium metaborate, sodium diborate, tetraborate), The borate minerals may include, for example, sodium borate, sodium pentaborate, sodium hexaborate, sodium octaborate), lead borate (e.g., lead metaborate, lead hexaborate), nickel borate (e.g., nickel orthoborate, nickel diborate, nickel tetraborate, nickel octaborate), barium borate (e.g., barium orthoborate, barium metaborate, barium diborate, barium tetraborate), bismuth borate, magnesium borate (e.g., magnesium orthoborate, magnesium diborate, magnesium metaborate, trimagnesium tetraborate, pentamagnesium tetraborate), manganese borate (e.g., manganese (I) borate, manganese metaborate, manganese tetraborate), lithium borate (e.g., lithium metaborate, lithium tetraborate, lithium pentaborate), salts thereof, or combinations thereof. Borate minerals may include, for example, borax, kainite, kainite, suanite, and szaibelyite. Among them, borax, boric acid and sodium borate (eg, sodium metaborate, sodium diborate, sodium tetraborate, sodium pentaborate, sodium hexaborate and sodium octaborate) are preferably used.
[0025] On the other hand, the present invention provides a film formed by the ethylene-vinyl ester copolymer saponified pellets as described above. Suitable methods and equipment for preparing the film formed by the ethylene-vinyl ester copolymer saponified pellets may include methods and equipment that are easily understood by those of ordinary skill in the art. The film preferably has highly uniform gas barrier properties. The gas barrier properties of the film can be evaluated by measuring the oxygen transmission rate (OTR) of the film. The gas barrier properties of the film can be measured using an OX-TRAN Model 2 / 21 oxygen transmission rate tester (manufactured by mocon) according to ISO 14663-2 method. In certain embodiments, the film has an oxygen transmission rate of less than 3.4, such as less than 3.4, less than 3, less than 2.8, less than 2.6, less than 2.4, less than 2.2, less than 2, less than 1.8, less than 1.6, less than 1.4, less than 1.2, less than 1, less than 0.8, less than 0.6, or less than 0.4, at 23°C and 65% relative humidity according to ISO 14663-2. 14663-2 At 23°C and 65% relative humidity, the oxygen permeability of the film is 0.05-3, for example: 0.05-3, 0.05-2.7, 0.05-2.5, 0.05-2.3, 0.05-2.1, 0.05-1.9, 0.05-1.7, 0.05-1.5, 0.05-1.3, 0.05-1.1, 0.05-0.9, 0.05~0.7、0.05~0.5、0.1~3、0.1~2.7、0.1~2.5、0.1~2.3、0.1~2.1、0.1~1.9、0.1~1.7、0.1~1.5、0.1~1.3、0.1~1.1、0.1~0.9、0.1~0.7、0.1~0.5、0.3~3、0.3~2.7、0.3 ~2.5、0.3~2.3、0.3~2.1、0.3~1.9、0.3~1.7、0.3~1.5、0.3~1.3、0.3~1.1、0.3~0.9、0.3~0.7、0.3~0.5、0.5~3、0.5~2.7、0.5~2.5、0.5~2.3、0.5~2.1、0.5~1.9、0.5~1. 7. 0.5-1.5, 0.5-1.3, 0.5-1.1, 0.5-0.9, 1-3, 1-2.7, 1-2.5, 1-2.3, 1-2.1, 1-1.9, 1-1.7, 1-1.5, 1.2-3, 1.2-2.7, 1.2-2.5, 1.2-2.3, 1.2-2.1, 1.2-1.9, 1.2-1.7 or 2-3.
[0026] In another aspect, the present invention provides a film formed from the above-mentioned ethylene-vinyl ester copolymer saponified pellets. In certain embodiments, the number of gels in the film is less than 1180 / m 2 , for example, less than 1180 pieces / m 2 Less than 1000 pieces / m 2 Less than 900 pieces / m 2 Less than 800 pieces / m 2 Less than 700 pieces / m 2 Less than 600 pieces / m 2 Less than 700 pieces / m 2 Less than 500 pieces / m 2 Less than 400 pieces / m 2 Less than 300 pieces / m 2 Less than 200 pieces / m 2 Or less than 100 pieces / m 2 In a preferred embodiment, the number of gels in the membrane is less than 600 / m 2 Less than 550 pieces / m 2 Less than 500 pieces / m 2 Less than 450 pieces / m 2 Less than 400 pieces / m 2 Less than 350 pieces / m 2 Less than 300 pieces / m 2 Less than 250 pieces / m 2 Less than 200 pieces / m 2 Less than 150 pieces / m 2 Or less than 100 pieces / m 2 .
[0027] In another aspect, the present invention provides a multilayer structure having at least one layer formed of pellets of the ethylene-vinyl ester copolymer saponified product of the present invention; at least one polymer layer; and at least one adhesive layer. The polymer layer may be selected from a low-density polyethylene layer, a polyethylene grafted maleic anhydride layer, a polypropylene layer, a nylon layer, and a combination thereof. The adhesive layer may be a tie layer, such as ARKEMA OREVAC 18729 from ARKEMA.
[0028] Example
[0029] The following non-limiting examples of various aspects of the present invention are provided primarily to illustrate various aspects of the present invention and the effects achieved therewith.
[0030] Example 1
[0031] The following provides a non-limiting method for preparing EVOH particles formed from EVOH resin compositions. Seven non-limiting example EVOH resin compositions (Examples EVOH 1-7) and eight comparative example EVOH resin compositions (Comparative Examples EVOH 1-8) were prepared according to methods similar to those disclosed below. However, the specific methods for preparing Example EVOH 1-7 and Comparative Examples EVOH 1-8 will generally differ from the methods disclosed below in one or more aspects.
[0032] Ethylene, vinyl acetate (VAM), methanol and initiator are added into a reactor and polymerized under specific conditions. A large amount of initiator is added during the polymerization to react. The polymerized material contains a large amount of initiator. An inhibitor is added to terminate the reaction. After the polymerization, the ethylene-vinyl acetate copolymer (hereinafter referred to as "EVAC") solution is mixed with the polymerization inhibitor using a special mixer. After mixing, the solution is subjected to procedures such as stripping, alkalization, granulation and drying to make EVOH particles / pellets.
[0033] Specifically, ethylene-vinyl acetate copolymer with a specific ethylene content is saponified with a saponification degree of 99.5% to prepare EVOH polymer. Subsequently, EVOH is dissolved in a solution containing methanol and water (ratio 70:30). After that, the EVOH solid content of the solution is 41wt.%, and the solution is placed at 60°C.
[0034] The solution of methanol, water and EVOH is then pelletized by underwater pelletization. Specifically, a pump is used to pump the solution of methanol, water and EVOH into a feed pipe at a flow rate of 120 L / min, and then fed into an input pipe with a diameter of 2.8 mm, and cut with a rotary knife at 1500 rpm. 5°C water is added to cool the EVOH pellets. Subsequently, the EVOH pellets are centrifuged to separate the EVOH particles. The separated EVOH particles are washed with water, and then dried through 3 different dryer combinations (as shown in Table 1) to obtain EVOH pellets.
[0035] Example 2
[0036] Films were formed using Example EVOH pellets 1-7 according to the following method. Example EVOH pellets 1-7 and Comparative Example EVOH pellets 1-8 were fed into a single-layer T-die cast film extruder (optical control system MEV4) to prepare films. The thickness of the films formed by Example EVOH pellets 1-7 and Comparative Example EVOH pellets 1-8 was 20 μm each. The temperature of the extruder was set to 220°C, and the temperature of the mold (i.e., the T-die) was set to 230°C. The rotation frequency of the screw was 7 rpm (rotations / minutes).
[0037] Example 3
[0038] Example EVOH pellets 1-7 and Comparative Example EVOH pellets 1-8 were evaluated to determine the properties of these EVOH pellets and films formed therefrom. As described above, Example EVOH pellets 1-7 and Comparative Example EVOH pellets 1-8 were prepared according to a method similar to that described in Example 1 above. However, the method for preparing EVOH pellets 1-8 differed in the following aspects for the prepared EVOH pellets:
[0039] Experimental changes in polymerization: polymerization temperature, polymerization pressure, VAM / methanol ratio;
[0040] Experimental changes for inhibitor addition: ratio of inhibitor to initiator, type of inhibitor;
[0041] Experimental changes in the mixing of polymerization discharge and inhibitor: mixer type, mixer length;
[0042] Experimental changes for desing, alkalization, and filtration after adding water: whether to filter.
[0043] The experimental process variables are summarized in Table 1.
[0044] Table 1
[0045] Parameter variables Variable range Inhibitor dosage (ppm) 10~1000 Inhibitor Addition Type Conjugated polyenes Inhibitor mix type Dynamic mixer or static mixer Mixer length (L / D) 1.3~65 <![CDATA[Mixer pressure drop (KG / cm 2 )]]> 0.02~1.2 Polymer viscosity (cp) 420~1500 <![CDATA[Reaction pressure (KG / cm 2 )]]> 28~70 Reaction temperature 40~90℃ Methanol / VAM ratio 5~60 Initiator addition amount (ppm) 50~500 Solid content of discharge (%) 10~70
[0046] The turbidity value of the EVOH pellets in methanol aqueous solution was further evaluated. Films were formed from Example EVOH 1-7 and Comparative Example EVOH 1-8, respectively, in a manner similar to that described in Example 2, and the films were analyzed to evaluate the amount of gel and oxygen permeability.
[0047] Table 2 provides the polymerization conditions, inhibitor addition conditions and an overview of some properties (i.e., EVOH inhibitor content, turbidity in methanol water) of Example EVOH pellets 1-4 and Comparative Example EVOH pellets 1-4; Table 3 provides the polymerization conditions, inhibitor addition conditions and some properties of Example EVOH pellets 5-7 and Comparative Example EVOH pellets 5-8, as well as the gel production and oxygen permeability of the films formed by Example EVOH 1-7 and Comparative Example EVOH 1-8.
[0048] Table 2
[0049]
[0050]
[0051] Table 3
[0052]
[0053] In order to evaluate the turbidity of Example EVOH 1-7 and Comparative Example EVOH 1-8, about 2.5g of EVOH sample was weighed and placed in a 250mL conical flask, 84g of methanol water (50.3g of methanol plus 33.6g of water) was prepared, and the prepared methanol water was added to the 250mL conical flask, and the solvent and sample in the conical flask were heated and refluxed for 2 hours until dissolved (heating plate temperature 450°C), and after dissolution, the heating plate was lowered to 60°C, and then the solution was tested according to the ISO 7027 method, and the measuring instrument was TurbidimeterHI98703. According to the above method, after the EVOH pellets are added to methanol / water, the solution becomes turbid because the trace aggregates in the EVOH particles are insoluble in methanol / water, and the aggregate content can be analyzed by a turbidity meter.
[0054] The gel formation of the films formed from Example EVOH 1-7 and Comparative Example EVOH 1-8 was evaluated. After the EVOH was processed into a single-layer film, the number of gels in the single-layer film was analyzed using FSA-100, and the gels with a size of less than 100 μm were mainly analyzed.
[0055] The oxygen transmission rate (OTR) of the film formed by Example EVOH 1-7 and Comparative Example EVOH 1-8 was evaluated. After the EVOH was processed into a single-layer film, the gas barrier property was tested by OTR. The test method was based on ISO 14663-2. The test conditions were 23°C / 65%RH. The measuring instrument was OXTRAN 2 / 21, manufactured by Mocon. The unit is cm 3 *20μm / m 2 *24Hr*atm.
[0056] The results show that the ethylene content of Example EVOH 1-4 is 24% to 35%, and the number of gels in the film formed by Example EVOH 1-4 is 75 to 432 / m 2 ) are much lower than the number of gels in the films formed by EVOH 1-4 in comparative examples (1342 to 2464 / m 2 ). It shows that no matter how the polymerization conditions and inhibitor addition conditions change, EVOH with an ethylene content of 36% to 48% can achieve the desired effect at a methanol-water ratio of 60% as long as the turbidity of methanol-water is kept below 300 NTU.
[0057] Example EVOH 5-7 has an ethylene content of 36% to 48%. The number of gels in the film formed from Example EVOH 5-7 (110 to 240 / m 2 ) are much lower than the number of gels in the films formed by EVOH 5-8 in comparative examples (1180 to 1962 per m 2 ). It shows that no matter how the polymerization conditions and inhibitor addition conditions change, EVOH with an ethylene content of 36% to 48% can achieve the desired effect at a methanol-water ratio of 80%, as long as the turbidity of the methanol-water is kept below 200 NTU.
[0058] According to the results of the examples, the reasons for the generation of aggregates are quite complicated. They may be affected by the mixer type, mixer length, inhibitor addition amount, inhibitor addition type, reaction temperature, reaction pressure, methanol / VAM ratio, etc., and the size of the aggregates produced varies greatly. Even if a filter is used, the aggregates cannot be effectively removed. As can be seen from Comparative Examples EVOH 3, 7 and 8, even if a 20 or 100 μm mesh filter is used for filtration during the preparation of EVOH, the amount of gel in the film formed by Comparative Examples EVOH 3, 7 and 8 is still quite high, exceeding the expected range of the present invention. Although not limited by any particular theory, the present invention has found that the turbidity of the prepared EVOH dissolved in methanol water is controlled within a specific range, indicating that it is an EVOH with a good mixture of inhibitor and polymer, the content of aggregates in this EVOH is low, and the amount of gel after subsequent film formation is small.
[0059] In addition, the oxygen permeability of the film formed from Example EVOH 1-7 was about 0.1 to 2.4 cm 3 *20μm / m 2 *24Hr*atm, the oxygen permeability of the film formed by the comparative example EVOH 1-8 is about 3.4~10.1cm 3 *20μm / m 2*24Hr*atm. The test results of the present invention show that as long as the turbidity of the prepared EVOH dissolved in methanol water is controlled within a specific range, the oxygen permeability of the film formed by the EVOH can be reduced. As shown in Tables 2 and 3, the turbidity of the comparative example EVOH 1-8 dissolved in methanol water exceeds the expected range described herein, and the test results show that the films formed by the comparative example EVOH 1-8 all have a relatively high oxygen permeability (about 3.4 to 10.1 cm 3 *20μm / m 2 *24Hr*atm). The EVOH film with low oxygen permeability can be used to produce various films, sheets and packaging containers with high oxygen barrier properties.
[0060] In summary, the ethylene-vinyl ester copolymer saponified pellets of the present invention have a specific turbidity value in methanol water, especially the ethylene content is 24-35 mole%, and the turbidity of the pellets dissolved in 60% (w / w) methanol aqueous solution is less than 300 NTU; or the ethylene content is 36-48 mole%, and the turbidity of the pellets dissolved in 80% (w / w) methanol aqueous solution is less than 200 NTU. In the manufacturing process of ethylene-vinyl ester copolymer saponified, if the inhibitor is not added enough or the polymerization output and the inhibitor are not mixed evenly, a large amount of gel will be generated after film formation. In view of this, the inventors found that no matter how the polymerization conditions and inhibitor addition conditions change, as long as the turbidity value of the ethylene-vinyl ester copolymer saponified pellets dissolved in methanol water is within the desired range, the content of aggregates in the ethylene-vinyl ester copolymer saponified pellets can be ensured to be low, thereby achieving the purpose of reducing the amount of gel generated after film formation and lowering the oxygen permeability.
[0061] Herein, all ranges provided are intended to include each specific range within a given range and combinations of sub-ranges between the given ranges. In addition, unless otherwise stated, all ranges provided herein include the endpoints of the ranges. Thus, ranges 1-5 specifically include 1, 2, 3, 4, and 5, as well as sub-ranges such as 2-5, 3-5, 2-3, 2-4, 1-4, etc.
[0062] All publications and patent applications cited in this specification are incorporated herein by reference, and each individual publication or patent application is specifically and individually indicated to be incorporated herein by reference for any and all purposes. In the event of any inconsistency between this document and any publication or patent application incorporated herein by reference, this document controls.
[0063] As used herein, the terms "including", "having" and "comprising" have an open, non-restrictive meaning. The terms "a", "an" and "the" should be understood to cover the plural as well as the singular. The term "one or more" means "at least one" and can therefore include a single feature or a mixture / combination of features.
[0064] Except in the operating examples or where otherwise indicated, all numbers indicating amounts of ingredients and / or reaction conditions may in all cases be modified by the term "about", meaning within ±5% of the indicated number. As used herein, the terms "substantially free" or "substantially free" refer to less than about 2% of a particular feature. All elements or features that are positively described herein may be negatively excluded from the claims.
Claims
1. An ethylene-vinyl ester copolymer saponified pellet, characterized in that: The ethylene content is 24-35 mole%, and the turbidity of the pellets in a 60% (w / w) methanol aqueous solution is less than 300 NTU; or the ethylene content is 36-48 mole%, and the turbidity of the pellets in a 80% (w / w) methanol aqueous solution is less than 200 NTU; the pellets include a polymerization inhibitor, the content of which is 1-850 ppm.
2. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, characterized in that: The ethylene content is 24-35 mole%, and the turbidity of the pellets dissolved in 60% (w / w) methanol aqueous solution is 0.5-120 NTU; or the ethylene content is 36-48 mole%, and the turbidity of the pellets dissolved in 80% (w / w) methanol aqueous solution is 0.5-120 NTU.
3. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, characterized in that: The polymerization inhibitor content is 5 to 650 ppm.
4. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, characterized in that: The polymerization inhibitor is a conjugated polyene.
5. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, characterized in that: The polymerization inhibitor is sorbic acid, cinnamic acid, 1,3-hexadiene or myrcene.
6. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, characterized in that: The polymerization inhibitor is added and mixed through a mixer, which is a dynamic mixer or a static mixer.
7. The ethylene-vinyl ester copolymer saponified pellets according to claim 6, characterized in that: The length to diameter ratio of the mixer is 1.3~65 L / D.
8. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, wherein: It has a boron content between 10-450 ppm.
9. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, wherein: It further comprises one or a combination of the group consisting of alkali metals, lubricants and alkaline earth metals.
10. The ethylene-vinyl ester copolymer saponified pellets according to claim 1, wherein: The saponification degree of the ethylene-vinyl ester copolymer saponified pellets is greater than 99.5 mol%.
11. An ethylene-vinyl ester copolymer film, characterized in that: The pellets are formed from the saponified ethylene-vinyl ester copolymer pellets according to any one of claims 1 to 10.
12. The ethylene-vinyl ester copolymer film according to claim 11, wherein According to ISO 14663-2 at 23°C and 65% relative humidity, the oxygen transmission rate of the film is less than 3.4 cm 3 *20 μm / m 2 *24Hr*atm.
13. The ethylene-vinyl ester copolymer film according to claim 11, wherein The number of gels in the membrane is less than 1180 / m 2 .
14. The ethylene-vinyl ester copolymer film according to claim 11, wherein The number of gels in the membrane is less than 600 / m 2 .
15. A multi-layer structure, characterized in that: include: (a) at least one layer is formed of pellets of the ethylene-vinyl ester copolymer saponified product according to any one of claims 1 to 10; (b) at least one polymer layer; and (c) at least one adhesive layer.
16. The multilayer structure according to claim 15, characterized in that The polymer layer is selected from the group consisting of a low-density polyethylene layer, a polyethylene grafted maleic anhydride layer, a polypropylene layer and a nylon layer, and the adhesive layer is an adhesive layer.
Citation Information
Patent Citations
Resin composition containing ethylene-vinyl alcohol copolymer
CN104220518A
Ethylene-vinyl alcohol copolymer composition pellets and method for producing ethylene-vinyl alcohol copolymer composition pellets
CN110139890A